Probing the curvature of the cosmos from quantum entanglement due to gravity - Suddhasattwa Brahma; Abhinove N. Seenivasan (Physics Letters B)
If gravity is fundamentally quantum, any two quantum particles must get entangled with each other due to their mutual interaction through gravity. This phenomenon, dubbed gravity-mediated entanglement, has led to recent efforts of detecting perturbative quantum gravity in table-top experimental setups. In this paper, we generalize this to imagine two idealized massive oscillators, in their ground state, which get entangled due to gravity in an expanding universe, and find that the curvature of the background spacetime leaves its imprints on the resulting entanglement profile. Thus, detecting gravity-mediated entanglement from cosmological observations will open up an exciting new avenue of measuring the local expansion rate of the cosmos.